The Relationship Between Sugar-Sweetened Beverage Consumption And Metabolic Syndrome Incidence In Adolescents: A Narrative Review - Nihana Aura Aprisano Dewi Dewi (CV. AFDIFAL MAJU BERKAH, 2026)
Metabolic syndrome in adolescents encompasses central obesity, hypertension, insulin resistance, and dyslipidemia, often associated with unhealthy lifestyles. In Indonesia, adolescents frequently consume sugar-sweetened beverages (SSBs), sometimes more than once a day, raising health concerns. This narrative review aims to examine the association between SSB consumption and the incidence of metabolic syndrome in adolescents. A literature search was conducted in PubMed, ScienceDirect, Google Scholar, and Springer using relevant keywords. Articles published between 2015 and 2025, written in English, and representing original research were included in this review. Evidence suggests that high SSB consumption is associated with an increased risk of metabolic syndrome. Frequent consumption contributes to central obesity through excess calorie intake. SSB consumption is also associated with insulin resistance, increased LDL and triglyceride levels, decreased HDL levels, and higher blood pressure. A dose-response pattern suggests that even moderate daily consumption ( 90 ml) may increase risk over time. High SSB consumption contributes to the risk of metabolic syndrome among adolescents. Reducing consumption is crucial to prevent long-term metabolic disorders.